Digital-Based Science Learning in Elementary Schools in Indonesia: A TPACK-Based Systematic Literature Review (SLR) - Jiwanjaya, Yoga (Global Action and Education for Society, 2026)
This article is a Systematic Literature Review (SLR) that aims to explore Technology Pedagogical Content Knowledge (TPACK) towards digital-based science learning in Indonesian elementary schools. This review uses PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to analyze articles retrieved from Google Scholar using the Publish or Perish 8 application. A total of 83 articles were identified using the keywords “digital” OR “teknologi” OR “video” OR “multimedia” OR “internet” OR “elearning” OR “interaktif” OR “animasi” OR “TPACK” OR “online” OR “daring” AND “model” OR “strategi” OR “pendekatan” AND “IPA” AND “SD” OR “MI” entered into the Publish or Perish 8 keyword. After conducting content analysis according to the TPACK framework, 14 articles were obtained which were used for this study. The results showed that elementary school teachers in Indonesia generally demonstrated adequate mastery of TPACK in science learning. The most widely used type of digital learning was multimedia video combined with learning models. Furthermore, the implementation of TPACK-based digital learning can improve learning outcomes, student interest, and student activity in science learning in Indonesian elementary schools.